Desarrollo de un módulo de pruebas de diagnóstico para motores trifásicos Bazuu 4651/4 en la Empresa Pública de Transporte de Pasajeros - Fares Palma, Ángel Diego (2018)
The following project was born from the need of the Metropolitan Public Company of Public Transportation of Quito - Trolley Bus, to give solution to the maintenance of the 4-pole Bazuu 4651 / 4 asynchronous electric motors, in its workshops and personnel in charge of the maintenance of the fleet 1 and 2 that make up the 120 trolleybus units. The problem for which the project was developed is mainly the electrical consumption of the Bazuu 4651/4 engines with 230 kW of power and its starting amperage, so it was not possible to connect them directly to the electrical network of the Trolley workshops. Bus without a bank of tests that allows a previous and progressive control and that also allows the visualization of the electrical data generated in real time of this variety of engines. Being able to obtain information about electrical defects before installing the Bazuu 4651/4 engine in the Trolleybus, allows the saving of resources in the economic and operational part, since this way it allows knowing if the engine meets the basic requirements for its operation and start-up, in turn make corrections in an efficient and appropriate way of the engine, therefore do not cause delays in the operation of the units when you want to start them. The information available for the maintenance of the Traction Motor Bazuu 4651/4 106.094 096.TDE-4 could not be verified without a test bench, for this reason its theoretical data were not taken as a standard for preventive and corrective maintenance in the engines that the project developed.